THE EFFECTIVENESS OF REPRODUCTIVE HEALTH EDUCATION CHATBOT ON ANEMIA PREVENTION KNOWLEDGE AND ATTITUDES IN JUNIOR HIGH SCHOOL GIRLS IN MAKASSAR CITY - Nurhayati (Fakultas Keguruan Dan Ilmu Pendidikan Universaitas PGRI Banyuwangi, 2026)
Anemia in adolescent girls remains a significant health issue in Indonesia, affecting growth, academic performance, and future reproductive health. It also increases the risk of complications during pregnancy. Digital tools such as chatbots offer an innovative approach to health promotion by providing interactive, accessible, and tailored education that meets adolescents' needs. Various studies have demonstrated that digital interventions, including chatbots, can effectively enhance adolescents' knowledge of reproductive health and anemia prevention.This study aimed to evaluate the effectiveness of a reproductive health education chatbot in improving knowledge and attitudes regarding anemia prevention among junior high school students in Makassar City. A quantitative pre-experimental design with a one-group pretest-posttest approach was employed. The sample consisted of 60 female students selected through purposive sampling. Data were collected using knowledge and attitude questionnaires, along with chatbot usage logs, and analyzed using univariate analysis, the Shapiro-Wilk test for normality, and the Paired Sample t-Test. The results showed a significant increase in mean knowledge scores from 63.42 ± 9.85 to 84.27 ± 7.31, and mean attitude scores improved from 65.18 ± 8.92 to 86.14 ± 6.75. The Paired Sample t-test revealed a statistically significant difference with a p-value of 0.001. In conclusion, the reproductive health education chatbot effectively improves knowledge and attitudes regarding anemia prevention among adolescent girls, suggesting its potential as a scalable digital health education tool.